Development of a Porcine Full-Thickness Burn Hypertrophic Scar Model and Investigation of the Effects of Shikonin on Hypertrophic Scar Remediation - Deng, Xingwang; Chen, Qian; Qiang, Lijuan; Chi, Mingwei; Xie, Nan; Wu, Yinsheng; Yao, Ming; Zhao, Dan; Ma, Jiaxiang; Zhang, Ning; Xie, Yan (Frontiers in Pharmacology, 2018)
Hypertrophic scars formed after burns remain a challenge in clinical practice. Development of effective scar therapies relies on validated animal models that mimic human hypertrophic scars. A consistent porcine full-thickness burn hypertrophic scar model has yet to be developed. We have previously reported that Shikonin induces apoptosis and reduces collagen production in hypertrophic scar fibroblasts in vitro and may therefore hold potential as a novel scar remediation therapy. In this study, we aimed to validate the potential of Shikonin on scar remediation in vivo. A novel porcine hypertrophic scar model was created after full-thickness burn wounds, and the effect of Shikonin on scar remediation was investigated. Clinical scar assessments, histology and immunohistochemistry were used to evaluate scar appearance, morphology and protein expression. Eight weeks after scar formation, clinical scar assessment indicated that the score of hypertrophic scars treated with Shikonin was significantly lower than that of the control group. Hypertrophic scars treated with Shikonin appeared flat, pink, and pliable. In addition, histological analysis indicated that hypertrophic scars treated with Shikonin exhibited reduced thickness of the epidermis and dermis, thin and even epithelial layers, reduced numbers of keratinocytes, uniform distribution of fibroblasts, and a parallel and loose arrangement of collagen fibers in the dermis. Moreover, immunohistochemical analysis indicated that Shikonin inhibited the expression of cytokeratin 10, p63, transforming growth factor-beta 1, alpha-smooth muscle actin and collagen I, which play important roles in hypertrophic scar formation. Based on these results, we conclude that Shikonin has potential as a novel scar therapy.